Pharmacological intervention of curcumin via the NLRP3 inflammasome in ischemic stroke - Du, Xiaoxue; Amin, Nashwa; Xu, Linhao; Botchway, Benson O. A.; Zhang, Bo; Fang, Marong (Frontiers in Pharmacology, 2023)
Ischemic-induced neuronal injury arises due to low oxygen/nutrient levels and inflammatory response that exacerbates neuronal loss. NOD-like receptor family pyrin domain containing 3 (NLRP3) is an important regulator of inflammation after ischemic stroke, with its inhibition being involved in nerve regeneration. Curcumin, a main active ingredient in Chinese herbs, plays a positive role in neuronal repair and neuroprotection by regulating the NLRP3 signaling pathway. Nevertheless, the signaling mechanisms relating to how curcumin regulates NLRP3 inflammasome in inflammation and neural restoration following ischemic stroke are unknown. In this report, we summarize the main biological functions of NLRP3 inflammasome along with the neuroprotective effects and underlying mechanisms of curcumin via impairment of the NLRP3 pathway in ischemic brain injury. The report also discusses the role of medicinal interventions targeting the NLRP3 and potential pathways, as well as possible directions for curcumin therapy to penetrate the blood brain barrier (BBB) and hinder inflammation in ischemic stroke. Conclusively, this report demonstrates that curcumin has neuroprotective properties by inhibiting inflammation and preventing nerve cell loss, thereby delaying the progression of ischemic brain damage.